The “Profitability” of Technology Licensing by U.S. Multinationals: A Framework for Analysis and an Empirical Study - Contractor, Farok J. (Journal of International Business Studies, 1980)
The fees or compensation charged by technology licensing companies to recipient firms overseas have long been subject to debate. Opinion has ranged from a cost-related pricing to a monopolistic pricing model where the price or compensation is considerably higher than the variable costs of effecting a transfer. The empirical study covering 102 technology licenses shows that whereas compensation levels greatly exceed transfer costs, statistically they are strongly related. Compensation levels are influenced by the extent of services rendered to the licensee and by his scale of production. Important differences were manifest between industrialized nations and LDCs, between product types, and between patented and unpatented technologies.